Checklist of the herpetofauna of Bukit Perangin Forest Reserve, Kedah, Malaysia - Ibrahim Jaafar; Zalina Awang; Shahriza Shahrudin; Shahrul Anuar Md Sah; Nur Hafizah Ibrahim; Amirah Hurzaid; Nurul Dalila Abdul Rahim; Mohd Abdul Min; Amirudin Ismail (Universiti Kebangsaan Malaysia, 2012)
Bukit Perangin Forest Reserve, Kedah Malaysia is a popular forest park well known for its clear rivers and streams, interesting sedimentary rock formations and a rich biodiversity in flora and fauna. However to date no report on the amphibians and reptiles of this forest has ever been published. Therefore, from January 2009 to May 2010, herpetofauna surveys were conducted at Bukit Wang Recreational Forest, which forms a part of the Bukit Perangin Forest Reserve. The results of the survey showed that a total of 15 species of amphibians belonging to 6 families and 15 species of reptiles belonging to 7 families were found in the study area. These constitute the first records for the amphibians and reptiles in this forest. The herpetofauna checklist showed that the most abundant amphibians were from the family Ranidae while the most abundant reptiles were from the family Gekkonidae.